PENERAPAN PENDIDIKAN KARAKTER MELALUI KEGIATAN KEDISIPLINAN SISWA SMP DARUL HAMIDIN PADAMARA LOMBOK TIMUR - Lalu Muhammad Ridho Firmansyah; Baiq Wimandari Safitri (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This article aims to describe how the implementation of character education through daily and weekly disciplinary activities for Darul Hamidin Middle School students, Padamara, East Lombok.  The approach used in this research is qualitative research with research procedures that produce qualitative-descriptive data.  In this study, data were collected using observations, interviews, audiovisuals, documentation, and various other reports.  This research was conducted in July-August 2021. In assessing the validity of the data from this study, the authors used the data of triangulation technique that was useful for achieving the research objectives obtained with the aim of checking or comparing data.  The results showed that with the character education, it was able to show the results of the application of discipline in the form of ceremonies every morning on Mondays and scouting activities every Saturday afternoon as weekly activities and Dhuha prayers and reading the holy  verses of the Qur'an was a daily activity before start the teacbing and learning activities  and then ended with the congregational midday prayer before leaving school.  This activity is carried out by the school with the habituation method on a regular basis in order to provide long-term effects for Darul Hamidin Middle School students towards advanced Indonesia.